Prevalence of obstructive sleep apnea in suicidal patients with major depressive disorder. (September 2019) - McCall, William V.; Benca, Ruth M.; Rumble, Meredith E.; Case, Doug; Rosenquist, Peter B.; Krystal, Andrew D.
Abstract: In this paper, we report the rate of previously undiagnosed obstructive sleep apnea (OSA) in a randomized clinical trial (RCT) of suicidal patients with major depressive disorder (MDD). One hundred and twenty-five suicidal adults with MDD were recruited into a RCT. None were suspected to have OSA. Fourteen percent met diagnostic criteria for OSA. The Apnea Hypopnea Index (AHI) was predicted by increasing age, male sex, and higher Body Mass Index. However, neither the degree of daytime sleepiness nor the degree of insomnia predicted AHI severity. A high degree of suspicion is warranted for OSA in suicidal patients with MDD, and for patients with treatment-resistant depression. ClinicalTrials.gov identifier: NCT01689909